The Relationship between Diagenetic Evolution and Hydrocarbon Charge in Deep Tight Reservoirs: A Case Study from Kepingtage Formation of S9 Well Block in Tarim Basin - Yukai Qi; Huixi Lin; Fushun Zhang; Xiuxiang Zhu; Hanwen Hu; Bo Zhou; Qing Wei (Geofluids)
The Silurian Kepingtage Formation of Tarim Basin is an important deep clastic reservoir. Exploration practice shows that the reservoirs are generally characterized by extremely low porosity and permeability, exhibiting strong mineral composition and physical property heterogeneities. The study of heterogeneity and its effect on oil charge is of great significance to the understanding of oil migration and accumulation in such reservoirs and thus is crucial to oil exploration. Therefore, based on identification and quantitative statistics of thin sections, SEM, and homogenization temperature measurements, this study was designed to examine the relationship between diagenetic evolution and oil emplacement in the Silurian Kepingtage Formation in S9 Block in Tarim Basin. The control of differential diagenesis and physical property evolution on oil charge process are discussed. It is found that the sandstones with fine grain size and high content of ductile grains (>20%) have experienced strong mechanical compaction, the porosity decreases rapidly in the early stage of burial. The densification process has been completed before the first period of oil charge so that no oil was found in the reservoir. In contrast, sandstones with relatively coarse grain size and low ductile grain content have better porosity and permeability properties, which are generally oil-bearing. This kind of sandstone generally experienced two periods of oil charge. Apart from moderate compaction, multiple diagenesis events were also observed, including quartz cementation, calcite cementation, and dissolution. Before the early period of oil charge, the diagenesis events are dominated by moderate compaction, chlorite cementation, and dissolution, and the reservoir property is still high. It seems that the time of late period oil charge is relatively long. With the growth of multiple types of authigenic minerals such as quartz, calcite, and illite after or sometimes synchronously occurred with the late period oil charge, the porosity gradually decreases.